OPTIMALISASI PENGELOLAAN OBJEK WISATA CANDI SUROWONO DI DESA CANGGU KECAMATAN BADAS KABUPATEN KEDIRI DI MASA PANDEMI COVID-19 - Alfiyah, Binti; Irmayant, Elis; Prasetyaningtyas, Efa Wahyu (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study is to describe the optimization of the financial management of the Surowono Temple tourist attraction in Canggu Village, Badas District. This research was conducted at the Surowono Temple in Canggu Village, Badas District, Kediri Regency. The method used in this research is descriptive qualitative method with data collection procedures consisting of observation, interviews and documentation. From the research carried out, it can be concluded that infrastructure management has been managed optimally by paying attention to the cleanliness and beauty of the tourist attraction. Meanwhile, financial management is still classified as not optimal because it has not used an online system in inputting visitor data, besides that the incoming and outgoing funds are still not clearly recorded. Meanwhile, the village government has made every effort to introduce Surowono Temple tourism both online through various social media and offline by making events on certain celebration days.